2017
DOI: 10.1021/acs.jpcb.6b10562
|View full text |Cite
|
Sign up to set email alerts
|

Interactions in Water–Ionic Liquid Mixtures: Comparing Protic and Aprotic Systems

Abstract: The sensitivity of ionic liquids (ILs) to water affects their physical and chemical properties, even at relatively low concentrations, yet the structural thermodynamics of protic IL- (PIL-) water systems at low water concentrations still remains unclear. Using the rigorous Kirkwood-Buff theory of solutions, which can quantify the interactions between species in IL-water systems solely from thermodynamic data, we have shown the following: (1) Between analogous protic and aprotic ILs (AILs), the AIL cholinium bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 112 publications
3
61
0
Order By: Relevance
“…In contrast to beneficial properties like low flammability, low volatility and low melting points, the use of ILs for practical purposes is often limited by their high hygroscopicity. Thus, even low amounts of water in the IL crucially influence the performance and modify thermophysical properties in addition to the structural organization of the solution when compared to pure ILs [8][9][10][11][12][13][14][15][16][17][18][19][20][21] . As a prominent example, the influence of water significantly diminishes the broad electrochemical window known for pure ILs, 19 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast to beneficial properties like low flammability, low volatility and low melting points, the use of ILs for practical purposes is often limited by their high hygroscopicity. Thus, even low amounts of water in the IL crucially influence the performance and modify thermophysical properties in addition to the structural organization of the solution when compared to pure ILs [8][9][10][11][12][13][14][15][16][17][18][19][20][21] . As a prominent example, the influence of water significantly diminishes the broad electrochemical window known for pure ILs, 19 .…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with previous results, it was reported that hydrophilic ILs show a tendency of pronounced water-anion network formation 31,32 and that even hydrophobic ILs attract high amounts of water 8,33 . The pronounced hygroscopicity of hydrophobic ILs was explained by the occurrence of water clusters at low and intermediate water mole fractions 20,21 . Although hygroscopic properties are typical for all IL classes, ranging from protic to aprotic ILs, a recent publication highlighted slight differences 21 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations